Pengaruh Pelatihan Dan Pengembangan Karir Terhadap Produktivitas Kerja Karyawan Pada One Third Consulting And Aboard Jakarta Pusat - Astri Novia Rahayu; Ibnu Sina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This research aims to determine the effect of training and career development on employee work productivity, both partially and simultaneously, at One Third Consulting and Abroad. The study employed a quantitative research method involving employees as the sample. The sampling technique used was saturated sampling, with a total of 55 respondents. The research applied several statistical tests, including the validity test, reliability test, classical assumption test, correlation coefficient test, regression coefficient test, coefficient of determination test, and hypothesis testing. The results of the study obtained the multiple regression equation: Y = 11.413 + 0.486X1 + 0.243X2 + e. The regression coefficient value of the performance variable (11.413) indicates that if training (X1) and career development (X2) remain unchanged, the consistency value of work productivity (Y) is 11.413. The t-test result for the effect of training on work productivity is 6.515 > 2.007 with a significance value of 0.000 < 0.05. Therefore, H0 is rejected and Ha is accepted, indicating that training has a positive and significant effect on employee work productivity. Meanwhile, the t-test result for the effect of career development on work productivity is 2.771 > 2.007 with a significance value of 0.008 < 0.05. This means H0 is rejected and Ha is accepted, indicating that career development also has a positive and significant effect on employee work productivity. Furthermore, the F-test result for the combined effect of training and career development on work productivity is 31.390 > 3.170 with a significance level of 0.000 < 0.05. This indicates that the hypothesis stating that training and career development simultaneously have a positive and significant effect on employee work productivity is accepted